How effective are mental health nurses in A&E departments?. Issue 9 (18th August 2006) - Sinclair, L; Hunter, R; Hagen, S; Nelson, D; Hunt, J
Abstract : Background: A&E departments are key points of contact for many people with mental health problems. Various models of care have been developed in A&E departments for delivering mental health services, but few have been assessed for effectiveness. The present study aimed to assess the impact of a dedicated A&E psychiatric nurse service on several outcomes relevant to patients and clinicians. Methods: A crossover design was used to introduce a dedicated psychiatric nurse service (comprising four experienced community psychiatric nurses) into two busy UK A&E departments. Standardised assessments were completed for each patient, and a random sample of these independently assessed for quality. Data were also collected on the number of patients assessed, psychiatric nurse time employed, waiting times, onward referrals, repeat attendances, patient satisfaction, and staff views. Results: A&E staff referred about a third of patients judged to have mental health problems to the psychiatric nurse service; approximately half of those assessed had a psychiatric history. On average, assessments took 60 min and over 90% of the formulated management plans were judged appropriate by independent assessors. The psychiatric nurse intervention had little impact on waiting times or satisfaction levels for mental health patients, although there was evidence of a change in onward referral patterns. Comment: Psychiatric nurse assessment services have been introduced in many A&E departments, although the evidence base for the effectiveness of this development is not well established. This study presents evidence that psychiatric nurses can provide an accurate assessment and referral service with advantages for patient care.